“A categoria é: Queer” - Pedagogias culturais Queers em processos (per)formativos de dança e educação - Castro, Crystian Danny da Silva (2025)
This methodological research seeks to investigate the potential of Queer Cultural Pedagogy in dance teacher training. To this end, an artistic-pedagogical process in dance was developed, inspired by the television series Pose and elements of Ballroom culture and Voguing dance—as cultural artifacts that dialogue with this dissident perspective—which culminated in the show “A Categoria é: Queer” (The Category is: Queer). In this context, the research seeks to reflect on the effects/affects of this process on dance teacher training, based on the perspectives of three educators who participated in the work, as well as the intersections developed by me as an artist-teacher-researcher. In a bricolage manner, multiple conceptual, aesthetic, poetic, artistic, educational, cultural, and sociopolitical aspects are woven into the discussions, permeated by autobiographical narratives and queer experiences, in order to understand the characteristics that involve Queer Cultural Pedagogy. Finally, Queer Cultural Pedagogy is highlighted as a methodological, artistic, and educational approach that mobilizes practices that are problematizing, subversive, and attuned to diversity, converging with contemporary dynamics regarding teacher training.